Student Records: Functions and Roles for Students and Alums - Ratih Surtikanti (Proceedings, 2022)
This study aims to describe students’ understanding of the function of the student record and PDDikti. Student records and PDDikti are instruments used to record student activities during their study and after graduation. Forlap Dikti is a reference for scholarships, research, and student level competitions in Indonesia. This research uses questionnaires distributed to more than 300 students from the records and archives management program to collect data. The results of this study provide an overview of students’ understanding of the function of PDDikti, including student records as vital evidence and awareness regarding the importance of student record management in higher education.